Global food insecurity. Treatment of major food crops with elevated carbon dioxide or ozone under large-scale fully open-air conditions suggests recent models may have overestimated future yields - Long, Stephen P (The Royal Society, 2005)
Predictions of yield for the globe's major grain and legume arable crops suggest that, with a moderate temperature increase, production may increase in the temperate zone, but decline in the tropics. In total, global food supply may show little change. This security comes from inclusion of the direct effect of rising carbon dioxide (CO(2)) concentration, [CO(2)], which significantly stimulates yield by decreasing photorespiration in C(3) crops and transpiration in all crops. Evidence for a large response to [CO(2)] is largely based on studies made within chambers at small scales, which would be considered unacceptable for standard agronomic trials of new cultivars or agrochemicals. Yet, predictions of the globe's future food security are based on such inadequate information. Free-Air Concentration Enrichment (FACE) technology now allows investigation of the effects of rising [CO(2)] and ozone on field crops under fully open-air conditions at an agronomic scale. Experiments with rice, wheat, maize and soybean show smaller increases in yield than anticipated from studies in chambers. Experiments with increased ozone show large yield losses (20%), which are not accounted for in projections of global food security. These findings suggest that current projections of global food security are overoptimistic. The fertilization effect of CO(2) is less than that used in many models, while rising ozone will cause large yield losses in the Northern Hemisphere. Unfortunately, FACE studies have been limited in geographical extent and interactive effects of CO(2), ozone and temperature have yet to be studied. Without more extensive study of the effects of these changes at an agronomic scale in the open air, our ever-more sophisticated models will continue to have feet of clay.